12S rRNA variation in the Malayan gaur (Bos gaurus hubbacki) and Indian gaur (Bos gaurus gaurus) - Siti Atika Abd. Khalim. (2012)
12S rRNA is a mitochondrial gene used for species determination in wild-life forensic biology. This study was conducted to determine the variation at the 12s rRNA gene in the Malayan gaur and Indian gaur using polymerase chain reaction (PCR). Fecal samples from three animals of each species were used to extract DNA. The DNA was amplified for partial region of the mtDNA 128 rRNA gene using specific primers. The PCR amplified a 712 bp DNA fragment for the three Malayan gaur and for only one of the Indian gaurs. The amplified PCR products from the four animals were sequenced and compared. Two of the Malayan gaur had similar sequences and this was also similar to the Indian gaur. The sequences of the gaurs differed from that of the Bos taurus and Bos indicus. Vitual digestion of the PCR products with the restriction enzymes EcoN1 and Taq1 revealed that these enzymes were not suitable for use in PCR-RFLP for identification of the Malayan gaur species.